WTO REGULATION OF TRANSNATIONAL PRIVATE AUTHORITY IN GLOBAL GOVERNANCE. Issue 4 (13th September 2018) - Du, Ming
Abstract: Following the proliferation of private standards in the global supply chain trade, it has become clear that these can have adverse effects on international commerce and world welfare in the same way that government-imposed mandatory regulations do. However, the scope of the obligation of WTO Members in relation to the regulation of private standards remains vague and open to divergent interpretations under WTO law. This article starts from the premise that the debate should move beyond the search for a reasonable interpretation of relevant WTO disciplines and instead begin to consider normative questions concerning the legitimacy and accountability of transnational private regulation in global governance and the potential role of the WTO in regulating such private authority. The article explores what justifies the role of the WTO, a multilateral intergovernmental organization, in regulating transnational private standards and how a regulatory mechanism might be designed and implemented in practice.